Immediate effect of Auricular Acupuncture on Electromyographic Activity and Muscle Strength of the Upper Trapezius Descending Fibers: Auricular acupoint and trapezium electromyography - Piccini, Adriana Arruda; Corrêa, Bruna; Mendonça, Gabriela Otília; Silva, Karina Braga; Santos, Adriana Teresa Silva; Terra, Andréia Maria Silva Vilela (Manual Therapy, Posturology & Rehabilitation Journal, 2023)
Introduction: Acupuncture is an ancient technique that, when applied to specific points on the body, triggers physiological responses in the muscle. Studies with surface electromyography began to correlate the electrical activity of skeletal striated muscles with acupuncture points, but there are still few studies with evidence. Objective: to analyze the immediate effect of auricular acupuncture on the electromyographic activity and muscle strength of trapezium descending fibers. Method: Clinical and prospective study, composed of a sample of 15 individuals, in which they participated in three stages: stage 1 corresponding to control, stage 2 - corresponding intervention and stage 3 corresponding to placebo. The instruments used for evaluation were surface electromyography and dynamometry of the trapezius muscle descending bilaterally during maximal voluntary isometric contraction. For the intervention, semipermanent needles were inserted into the auricular acupoints: Shemmen, Kidney, Sympathetic, shoulder and shoulder joint and to the placebo - the needle was inserted at the point of the trachea. The experiment was performed with a fixed interval of seven days between steps. The t-test and the Wilcoxon test were used for intragroup comparisons and the two-way ANOVA test for intergroup comparison. Results: there were significant intragroup reductions in trapezius muscle strength for downward intervention, however, for electromyographic activity there was no statistical difference. Conclusion: It is concluded that auricular acuponts decreased the force of the trapezius muscle downward fibers.